Marijuana: To Use or Not to Use - Banzal, Sonal; Kabadi, Dr. Udaya M (International Journal of Innovative Research in Medical Science, 2018)
Several state legislatures legalized marijuana for medicinal and recreational purposes despite federal government’s refusal to decriminalize it. Moreover, usage by over 9 % of population ages 12 years documented by CDC in 2016 may have promoted smuggling across state lines.[1,2]